Classroom Climate: Unique Dependent and Independent Variables - Cepi Safruddin Abdul Jabar; Hadianto; Grahita Kusumastuti; Wening Prabawati (Journal for Lesson and Learning Studies, 2023)
Class climate plays a dual role as a dependent and independent variable. As a dependent variable, the class climate is influenced by several variables. On the other hand, as an independent variable, the class climate is correlated with other variables. This research aims to confirm the studies that have been done before and ensure that these related variables must be increased or become the impact of increasing the classroom climate. This type of research is a literature study that explores more than 40 articles about classroom climate conducted in Indonesia and other countries. The data analysis technique used is descriptive qualitative analysis. The results of this study indicate that among the variables that influence or contribute to classroom climate are simulation strategies, student attitudes, teacher behaviour, and integration between media and learning approaches. Variables that are affected by classroom climate include student behaviour, student achievement, student motivation, learning outcomes, and bullying behaviour. Therefore, teachers and principals are recommended to increase the variables that affect classroom climate and the classroom climate itself because they will also affect other variables. This study convinces the reader that classroom climate is an intermediary variable which is a key factor for improving the learning process.